Science philanthropy, energy systems research, and societal responsibility: A match made for the 21st century. (February 2021) - Michelson, Evan S.
Abstract: An increasingly important and often overlooked issue in science and technology policy is recognizing the role that philanthropies play in setting the direction of research. In an era where public and private resources for science are strained, the practices that foundations adopt to advance basic and applied research needs to be better understood. A new book, Philanthropy and the Future of Science and Technology, is a first-of-its-kind study that provides a detailed assessment of the current state of science philanthropy, surveying the landscape of contemporary philanthropic involvement in science and technology by combining theoretical insights drawn from the responsible research and innovation (RRI) framework with empirical analysis investigating an array of examples and case studies. In particular, this analysis can inform how philanthropic funders of research focused on energy systems, environmental issues, and climate change can ensure that this scholarship is well positioned to have societal impact. Such philanthropic-supported research is needed to guide the design, development, and implementation of more effective, practical solutions and practices at multiple levels of decision-making. In doing so, this article details some of the new programmatic efforts focused on advancing energy and climate research that has emerged from the philanthropic community in recent years. This article concludes by exploring alternative future scenarios that highlight different ways in which the relationship between science philanthropy and societal responsibility might evolve going forward.